Influencing factors of hand, foot, and mouth disease among children in Guangdong province: a case-control study - Si-yi CHEN; Wei WU; Jie-wen PENG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore influencing factors of hand, foot, and mouth disease (HFMD) among children in Guangdong province and to provide evidences for developing comprehensive measures on HFMD prevention and control and mechanism. MethodsWith a self-designed questionnaire and face-to-face interview with the participants' legal guardians, we conducted a case-control study during May - July 2017. The cases were 339 children (177 boys and 162 girls aged 3.54 ± 1.17 years) initially diagnosed with HFMD at two hospitals in a prefecture and a county of Guangdong province; the controls were 339 hospital/community-matched children without diarrhea, gastroenteritis, history of suffering from HFMD, herpangina or other related diseases. ResultsCompared to the controls, the cases were reported with significantly higher proportions of with 3 or more children under the age of 14 years in the family (12.09% vs. 5.90%), taking Chinese patent medicine in the past month (13.57% vs.9.73%), sucking fingers frequently (18.29% vs. 10.06%), playing on the ground occasionally (55.46% vs. 44.97) or frequently (24.78% vs. 21.30%), spending 40 - 59 minutes in every physical activity (14.75% vs. 8.88%), and having a contact with someone suffering from HFMD in the past month (20.35% vs. 0.59%) but lower proportions of with paternal education of college and above (23.01% vs. 34.91%), with maternal education of college and above (20.65% vs. 31.86%), washing hands frequently before eating and after using toilet (70.50% vs. 84.91%), washing hands frequently after going out (60.18% vs. 76.33%), consuming food supplemented with prebiotics in the past month occasionally (18.88% vs. 23.96%) or frequently (2.65% vs. 12.43%), and drinking herbal tea occasionally (52.51% vs. 60.36%) or frequently (9.14% vs. 12.13%) (P < 0.05 for all). Unconditional multivariate logistic regression analysis revealed that significant risk factors of HFMD incidence included taking Chinese patent medicine in the past month, sucking fingers frequently, spending 20 - 59 minutes in every physical activity, and contacting with HFMD cases in the past month; while, consuming prebiotics frequently in the past month and drinking herbal tea occasionally were protective factors against HFMD incidence. ConclusionHFMD incidence is affected by many factors such as exposure to HFMD cases, hygiene habits, prebiotics consumption, and taking medicine among children in Guangdong province.